2007
DOI: 10.1097/jto.0b013e3180cc25b0
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Long-Lasting Tumor Control with Erlotinib after Progression with Gefitinib in Advanced Non-Small Cell Lung Cancer

Abstract: Erlotinib may be effective in patients with non-small cell lung cancer who were previously and successfully treated with gefitinib. However, careful selection of these patients is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…Several retrospective studies have described the clinical activity of one EGFR-TKI treatment after the failure of another [18,19,20,21,22,23,24] or readministration of the same drug [14,15,25]. Most such reports have noted favorable results, although Viswanathan et al [19 ]and Costa et al [24 ]reported no or only a limited response to erlotinib after progression on gefitinib.…”
Section: Discussionmentioning
confidence: 92%
“…Several retrospective studies have described the clinical activity of one EGFR-TKI treatment after the failure of another [18,19,20,21,22,23,24] or readministration of the same drug [14,15,25]. Most such reports have noted favorable results, although Viswanathan et al [19 ]and Costa et al [24 ]reported no or only a limited response to erlotinib after progression on gefitinib.…”
Section: Discussionmentioning
confidence: 92%
“…Tumor regression in the brain was observed in chemonaive patients as well as in relapse after previous gefitinib treatment and also in patients who were previously judged resistant to gefitinib and who were intermittently treated with chemotherapy. In addition, erlotinib has been successfully applied in patients with previous progression under gefitinib [17,18] but also the inverse sequence has been used with success [18]. One of the most exciting developments is the application of lapatinib, a dual tyrosine kinase inhibitor against both Her2=neu and EGFR in patients with breast cancers metastatic to the brain.…”
Section: Targeting Egfr and Her2=neu In Patients With Brain Metastasismentioning
confidence: 98%
“…It has previously been reported that certain cases achieved long-term disease control for >13 months with EGFR-TKI re-challenge (40,41). Certain clinical characteristics, including response or time to progression (TTP) to previous EGFR-TKI, chemotherapy between EGFR-TKIs, and EGFR-TKI free interval have been examined as predictive markers for the success of EGFR-TKI re-challenge (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%